Rancang Bangun Sistem Keamanan Pintu Menggunakan PIR Sensor dengan Image Notification Berbasis Internet Of Things - Subekti, Muhammad Yayang; Suprianto, Bambang; Rohman, Miftahur; Anifah, Lilik (Indonesian Journal of Engineering and Technology (INAJET), 2024)
Technological advancements have led to innovations in home security, crucial due to rising crime rates. In Blitar, East Java, with 130 criminal cases, including 25 aggravated thefts, home security still relies on standard locks without additional safeguards. This study designs a door security monitoring system using PIR sensors and IoT with image notifications. The research stages include data collection, needs analysis, system design, hardware and software development, testing, and evaluation. The system uses PIR sensors and MC-38 sensors to detect movement and door activity, sending notifications via Telegram. Test results show the system works well with average response times: 2.2 seconds for PIR detection, 6.8 seconds for image transmission, 1.3 seconds for the MC-38 sensor triggered from inside, and 6.8 seconds when triggered from outside. Notification delivery averages 9.2 seconds during the day and 4 seconds at night. The average request time for image data is 7.4 seconds and 1.8 seconds for temperature data, with a 0.458% error rate for temperature parameters. This study successfully developed an effective and efficient IoT-based door security monitoring system, providing a practical and innovative solution to enhance home security in Blitar.